1981
DOI: 10.1210/endo-108-6-2078
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone and Adenosine-3′,5′-Monophosphate Acutely Increase Phospholipids of the Phosphatidate-Polyphosphoinositide Pathway in Rabbit Kidney Cortex Tubulesin Vitroby a Cycloheximide-Sensitive Process*

Abstract: Parathyroid hormone (PTH) rapidly increased to concentrations of phosphatidic acid, phosphatidylinositol, diphosphoinositide, and triphosphoinositide during incubations of rabbit kidney cortical tubules in vitro. These effects were preceded by increases in cAMP, which also induced virtually identical increases in these phospholipids. Pretreating the tubules with cycloheximide inhibited these phospholipid effects of PTH and cAMP. These findings are similar to those reported for ACTH and cAMP in the adrenal cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…These results are of interest in relation to the reports by Budot-Lopez et al [14] and Farese et al [15]. They showed that PTH and dibutyryl cAMP acutely increased phos pholipids, i.e.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These results are of interest in relation to the reports by Budot-Lopez et al [14] and Farese et al [15]. They showed that PTH and dibutyryl cAMP acutely increased phos pholipids, i.e.…”
Section: Discussionsupporting
confidence: 76%
“…They showed that PTH and dibutyryl cAMP acutely increased phos pholipids, i.e. phosphatidic acid, phosphatidyinositol, phosphatidylinositol 4'-monophosphate and phosphati dylinositol 4',5'-bisphosphate, in rabbit kidney cortical tubules both in vivo and in vitro [14,15]. These anionic phospholipids are important brush-border gentamicin binding sites [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators (18)(19)(20)(21) have shown an effect of PTH on renal tubular phosphoinositide metabolism, and one report shows the effect was present in the apical membrane of the proximal renal tubule (18). Some have reported that the stimulation of phosphoinositide metabolism by PTH was cyclic AMP dependent (19). This would remove it from a mechanism of cell activation, and place it in the realm of a biologic response.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of hormones have been reported on membrane phospholipase A2, arachidonic acid, saturation of phospholipid acyl groups, phosphatidic acid, phosphoinositides, phosphatidylglycerol, and N-methyl transferases (16)(17)(18)(19)(20)(21). The changes in lipids shown to occur in plasma membranes by these hormones have been small, but small changes may produce significant effects through association with receptors or as annulus lipids for membrane proteins (22,23).…”
Section: Discussionmentioning
confidence: 99%